Gap-phase dynamics and succession in the shortgrass steppe - Coffin, Debra P., author; Lauenroth, William K., advisor; Redente, Edward F., committee member; Woodmansee, Robert George, committee member; Kirchner, Thomas B., committee member (Colorado State University. Libraries, 1988)
Previous conceptualizations of succession in shortgrass plant communities have focused on the effects of large-scale disturbances with the conclusion that the dominant plant species, blue grama [Bouteloua gracilis (H.B.K.) Lag. ex Griffiths] fails to recover after a disturbance. My overall objective was to apply a gap dynamics approach based on small, frequently-occurring disturbances to shortgrass plant communities with the hypothesis that the death of a fullsize B. gracilis plant results in a gap in the belowground resource space and initiates the successional processes of gap dynamics. I concluded that a gap dynamics conceptualization of shortgrass communities provides a promising alternative to a conceptual model that emphasizes the effects of large disturbances. My first objective was to evaluate the effects of three small, patch-producing disturbances (cattle fecal pats, western harvester ant mounds, and small animal burrows) on B. gracilis-dominated plant communities by developing a spatially-explicit simulation model. Propagating the effects of these disturbances through time suggested that B. gracilis is able to recover after small disturbances. My second objective was to evaluate the short-term successional dynamics on small disturbances. I conducted a field study to evaluate the effects of three types of disturbances and their associated characteristics of size, seasonality, and location by soil texture on the recovery of plants. The density and cover of plants on the two naturally-occurring disturbances (western harvester ant mounds and small animal burrows) were dominated by perennials one year after the disturbances occurred while the majority of the cover on the artificially-produced disturbances was attributed to annuals. My third objective was to evaluate the long-term successional dynamics on small disturbances and the time required for B. gracilis to recover after a disturbance. I developed a gap dynamics simulation model based on the belowground gap in the resource space that results when an individual B. gracilis plant dies. The faster recovery time of B. gracilis in the model than observed experimentally on large disturbances suggests that processes associated with the recovery of B. gracilis may be scale-dependent.
Keywords: Grassland ecology -- Mathematical models